2016 Moratuwa Engineering Research Conference (MERCon) 2016
DOI: 10.1109/mercon.2016.7480109
|View full text |Cite
|
Sign up to set email alerts
|

Support for traceability management of software artefacts using Natural Language Processing

Abstract: One of the major problems in software development process is managing software artefacts. While software evolves, inconsistencies between the artefacts do evolve as well. To resolve the inconsistencies in change management, a tool named "Software Artefacts Traceability Analyzer (SAT-Analyzer)" was introduced as the previous work of this research. Changes in software artefacts in requirement specification, Unified Modelling Language (UML) diagrams and source codes can be tracked with the help of Natural Languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…CICD can be applied to straightforwardly accomplish such requirements as in DevOps. In addition, the design and development of supporting tools to automate the MLOps process can be extended by incorporating natural language processing (NLP) as well [24]. The health of the models should be live monitored and precautions should be taken to reduce the impact on the production application.…”
Section: Current Challenges and Future Research Directionsmentioning
confidence: 99%
“…CICD can be applied to straightforwardly accomplish such requirements as in DevOps. In addition, the design and development of supporting tools to automate the MLOps process can be extended by incorporating natural language processing (NLP) as well [24]. The health of the models should be live monitored and precautions should be taken to reduce the impact on the production application.…”
Section: Current Challenges and Future Research Directionsmentioning
confidence: 99%
“…Most of the time, the textual content in the artefacts provides descriptive details about its informal semantics. The frequently involved pre-processing steps for textual-based requirements artefacts are Natural Language Processing (NLP) tasks such as tokenization, text normalization, anaphora analysis, morphological analysis and stemming [4] [21]. It is assumed that the artefacts are conceptually related if their textual contents are similar Thus, trace links can be created among them.…”
Section: A Information Retrieval and Data Pre-processingmentioning
confidence: 99%
“…The tool Software Artefact Traceability Analyser (SAT-Analyser) [21][48] has addressed the traceability among requirements artefact, UML class diagrams regarding the design artefact and the source code artefact in Java programming language. It has used NLP and traceability has been established based on a string similarity computation using the Jaro-Winkler algorithm and Levenshtein Distance algorithm along with WordNet synonyms and pre-defined dictionary ontology.…”
Section: B Related Studies On Traceability Managementmentioning
confidence: 99%
“…Alobaidi and Mahmood [73] found the relationship between requirement documents and others using semantic similarity and semantic relatedness. Arunthavanathan et al [75] used the NLP techniques to convert the natural language requirement document into XML format by extracting classes, methods, attributes and relationships and then used the XML format so generated in their tool ''Software Artefacts Traceability Analyser (SAT),'' which resolved the problem of artefacts traceability, that is, links between the artefacts like Requirements, UML Class Diagrams and Java code of the project, when a change occurs. Le et al [15] proposed the approach called RCLinker, where they found the link between the issue reports and the commit messages by considering the context along with comparing the text between these two artefacts.…”
Section: Traceabilitymentioning
confidence: 99%